Shikonin inhibits the cell viability, adhesion, invasion and migration of the human gastric cancer cell line MGC‐803 via the Toll‐like receptor 2/nuclear factor‐kappa B pathway. (16th April 2015) - Liu, Ji Ping; Liu, Dan; Gu, Jun Fei; Zhu, Mao Mao; Cui, Li
Abstract Objectives Shikonin is an active naphthoquinone pigment isolated from the root of Lithospermum erythrorhizon. This study was designed to explore the inhibition of Shikonin on cell viability, adhesion, migration and invasion ability of gastric cancer (GC) and its possible mechanism. Methods 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay was performed for cell viability and adhesion ability of MGC‐803 cells. Cell scratch repair experiments were conducted for the determination of migration ability while transwell assay for cell invasion ability. Western blot analysis and real‐time polymerase chain reaction assay were used for the detection of protein and mRNA expressions. Key findings Fifty per cent inhibitory concentration of Shikonin on MGC‐803 cells was 1.854 μm. Shikonin (1 μm) inhibited significantly the adhesion, invasion and migratory ability of MGC‐803 cells. Interestingly, Shikonin in the presence or absence of anti‐Toll‐like receptor 2 (TLR2) antibody (2 μg) and nuclear factor‐kappa B (NF‐κB) inhibitor MG‐132 (10 μm) could decrease these ability of MGC‐803 cells markedly, as well as the expression levels of matrix metalloproteinases (MMP)‐2, MMP‐7, TLR2 and p65 NF‐κB. In addition, the co‐incubation of Shikonin and anti‐TLR2/MG‐132 has a significant stronger activity than anti‐TLR2 or MG‐132 alone. Conclusions The results indicated that Shikonin could suppress the cell viability, adhesion, invasion and migratory ability of MGC‐803 cells through TLR2‐ or NF‐κB‐mediated pathway. Our findings provide novel information for the treatment of Shikonin on GC.